Progress on the Quality of Animal/Plant Protein and Fish Surimi Mixed Gel - Xinyue ZHANG; Wenhao GENG; Miaomiao TIAN; Xin LIANG; Xinrong LI; Xinru FAN; Qiancheng ZHAO (Shipin gongye ke-ji)
Gel properties play a crucial role in evaluating the quality of surimi products, which are favored by consumers for their high nutritional value, delightful taste, and convenient storage and transportation. However, with the rapid development of China's food manufacturing industry and the diversification of consumer groups, traditional surimi products are unable to satisfy the demands for a balanced diet and sensory characteristics. As a result, there is growing interest in developing novel surimi products, particularly in exploring the use of alternative animal- and plant-based raw materials to produce mixed surimi gel with expected gel properties. In this review, the research progress of animal and plant proteins and surimi gel formation mechanism is summarized. The animal and plant proteins can effectively improve the gel properties, water holding capacity and microstructure of surimi by promoting the cross-linking between proteins and inhibiting the activity of surimi protease, respectively is expounded. The issues of suboptimal sensory attributes and an ambiguous modification mechanism during the enhancement of mixed surimi product quality are identified. The aim is to provide theoretical support for the development of novel surimi products with improved gel properties while offering guidance for further advancements.